Hegemoni Kekuasaan Dalam Novel Ukhruj Minha Yâ Mal’ûn Karya Saddam Hussein (Kajian Hegemoni Gramsci) (Jurnal Adabiya, 2022)
This research is entitled Hegemony of Power in Saddam Hussein's Novel Ukhruj Minha Yâ Mal'ûn. This study aims to describe the ideological formations contained in the novel Ukhruj Minha Yâ Mal'ûn by Saddam Hussein. This type of research is descriptive qualitative. The data source of this research is the novel Ukhruj Minha Yâ Mal'ûn by Saddam Hussein. The data of this research are in the form of words, sentences that describe the ideological formation of the hegemony of power. Data collection techniques used reading and note-taking techniques. The data analysis technique uses content analysis. The results of this study include: first, the authoritarianism carried out by Hasqil by using the wife of a tribal chief to rule and influence the Roman chief and tribal leaders to achieve his goals. Second, the ideology of capitalism carried out by Hasqil's figure is by using his wealth so that he can rule and Hasqil also associates with the chiefs of the Roman tribes to dominate the market. Third, the ideology of vandalism that Hasqil carried out in order to achieve his goal of killing livestock and burning the gardens of the tribe's inhabitants.